Human Capital as Source of Building Competitiveness of State, its Economic and Social Development - N. P. Tishkina; E. V. Zakharova (Вестник Российского экономического университета имени Г. В. Плеханова)
Today the issue of shaping the human capital necessary for economy of knowledge is not only a topic of theoretical discussion, as it has become a leader in the global agenda of social and economic development. The leading countries consider human capital as the most important source of development, because in current situation it can speed up social and economic development, as well as competitiveness of state. The article shows topicality of the digital component of human capital and provides goals of developing human capital included in strategies of social and economic development of several regions of Russia. It also gives information about digital skills of the Russian population and some European countries. The structure of unemployed with different level of education in Russian regions is shown in dynamics. The authors prepared recommendations concerning competences necessary for economy of knowledge and for shaping infrastructure of regional systems of professional education.